El método jurídico constitucional y la STC 145/2015, de 25 de junio, como ejemplo de fallas en su implementación - Antonio Ibáñez Macías (Revista Vasca de Administración Pública)
In this paper we carry out an exhaustive analysis, from a methodological point of view, of STC 145/2015, of June 25. In it, we find numerous flaws in the implementation of the constitutional legal method in terms of respect for the text of the constitution, the following of precedent, the interpretative rule of article 10.2, the use of analogy, weighting, etc. The methodological failures, when they are numerous or serious, result in the discredit and delegitimization of the TC as guarantor of the Constitution and fundamental rights. It is therefore necessary for this institution to adhere to a rigorous legal method in the exercise of its jurisdictional activity.